Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Of course! Let's simplify the expression [tex]\(\sqrt{5 u w^5} \sqrt{15 u^8 w}\)[/tex] step by step, assuming all variables are positive real numbers.
1. Combine the expressions inside the square roots:
[tex]\[ \sqrt{5 u w^5} \sqrt{15 u^8 w} = \sqrt{(5 u w^5) (15 u^8 w)} \][/tex]
2. Multiply the expressions under the square root:
[tex]\[ \sqrt{(5 u w^5) (15 u^8 w)} = \sqrt{5 \cdot 15 \cdot u \cdot u^8 \cdot w^5 \cdot w} \][/tex]
3. Simplify the multiplication inside the square root:
[tex]\[ 5 \cdot 15 = 75 \][/tex]
[tex]\[ u \cdot u^8 = u^9 \][/tex]
[tex]\[ w^5 \cdot w = w^6 \][/tex]
So the expression becomes:
[tex]\[ \sqrt{75 u^9 w^6} \][/tex]
4. Break down the components of the square root:
[tex]\[ 75 u^9 w^6 \][/tex]
5. Simplify each component separately inside the square root:
[tex]\[ \sqrt{75} = \sqrt{25 \cdot 3} = 5 \sqrt{3} \][/tex]
[tex]\[ \sqrt{u^9} = u^{9/2} = u^4 \sqrt{u} \][/tex]
[tex]\[ \sqrt{w^6} = w^{6/2} = w^3 \][/tex]
6. Combine the simplified parts:
[tex]\[ \sqrt{75 u^9 w^6} = 5 \sqrt{3} u^4 \sqrt{u} w^3 \][/tex]
7. Combine like terms:
[tex]\[ 5 \sqrt{3} u^4 \sqrt{u} w^3 = 5 u^4 w^3 \sqrt{3u} \][/tex]
Therefore, the simplified expression is:
[tex]\[ \boxed{5u^4w^3 \sqrt{3u}} \][/tex]
1. Combine the expressions inside the square roots:
[tex]\[ \sqrt{5 u w^5} \sqrt{15 u^8 w} = \sqrt{(5 u w^5) (15 u^8 w)} \][/tex]
2. Multiply the expressions under the square root:
[tex]\[ \sqrt{(5 u w^5) (15 u^8 w)} = \sqrt{5 \cdot 15 \cdot u \cdot u^8 \cdot w^5 \cdot w} \][/tex]
3. Simplify the multiplication inside the square root:
[tex]\[ 5 \cdot 15 = 75 \][/tex]
[tex]\[ u \cdot u^8 = u^9 \][/tex]
[tex]\[ w^5 \cdot w = w^6 \][/tex]
So the expression becomes:
[tex]\[ \sqrt{75 u^9 w^6} \][/tex]
4. Break down the components of the square root:
[tex]\[ 75 u^9 w^6 \][/tex]
5. Simplify each component separately inside the square root:
[tex]\[ \sqrt{75} = \sqrt{25 \cdot 3} = 5 \sqrt{3} \][/tex]
[tex]\[ \sqrt{u^9} = u^{9/2} = u^4 \sqrt{u} \][/tex]
[tex]\[ \sqrt{w^6} = w^{6/2} = w^3 \][/tex]
6. Combine the simplified parts:
[tex]\[ \sqrt{75 u^9 w^6} = 5 \sqrt{3} u^4 \sqrt{u} w^3 \][/tex]
7. Combine like terms:
[tex]\[ 5 \sqrt{3} u^4 \sqrt{u} w^3 = 5 u^4 w^3 \sqrt{3u} \][/tex]
Therefore, the simplified expression is:
[tex]\[ \boxed{5u^4w^3 \sqrt{3u}} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.